Respuesta :

[tex]11x^2 - 4x = 1[/tex]
[tex]11x^{2} - 4x - 1 = 1 - 1[/tex]
[tex]11x^{2} - 4x - 1 = 0[/tex]
[tex]x = \frac{-(-4) \± \sqrt{(-4)^{2} - 4(11)(-1)}}{2(11)}[/tex]
[tex]x = \frac{4 \± \sqrt{16 + 44}}{22}[/tex]
[tex]x = \frac{4 \± \sqrt{60}}{22}[/tex]
[tex]x = \frac{4 \± 2\sqrt{15}}{22}[/tex]
[tex]x = \frac{2 \± \sqrt{15}}{11}[/tex]
[tex]x = \frac{2 + \sqrt{15}}{11}\ \bold{or}\ x = \frac{2 - \sqrt{15}}{11}[/tex]

Answer:

a - 2/11 + sqrt15/11

Step-by-step explanation:

trust me


ACCESS MORE